2015
DOI: 10.1038/labinvest.2014.161
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular colon cancer-associated Escherichia coli promote protumoral activities of human macrophages by inducing sustained COX-2 expression

Abstract: Intestinal dysbiosis has been reported in patients with colorectal cancer, and there is a high prevalence of Escherichia coli belonging to B2 phylogroup and producing a genotoxin, termed colibactin. Macrophages are one of the predominant tumor-infiltrating immune cells supporting key processes in tumor progression by producing protumoral factors such as cyclooxygenase-2 (COX-2). Here, we investigated whether B2 E. coli colonizing colon tumors could influence protumoral activities of macrophages. In contrast to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 63 publications
1
56
0
Order By: Relevance
“…As previously demonstrated,51 strain ED1a was killed by THP-1 macrophages, demonstrating efficient bactericidal activity of the cell lines (table 1). As expected, strain K12 was also killed, and strain LF82 resisted macrophage killing (table 1).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…As previously demonstrated,51 strain ED1a was killed by THP-1 macrophages, demonstrating efficient bactericidal activity of the cell lines (table 1). As expected, strain K12 was also killed, and strain LF82 resisted macrophage killing (table 1).…”
Section: Resultssupporting
confidence: 75%
“…Subramanian et al 57 also observed considerable overlap between the ability of CD and control isolates to replicate within macrophages, and Raisch et al 51 showed that 84% of colon cancer-associated B2 E. coli strains can survive and replicate within THP-1 macrophages. UPEC are also capable of intramacrophage replication 56.…”
Section: Discussionmentioning
confidence: 99%
“…This increased permeability, however, could also contribute to tipping the balance in favor of M2 TAMs. CRCassociated E. coli, but not commensal E. coli, has been shown to survive within macrophages derived from the THP-1 human monocyte cell line and to induce Cox-2 expression in these cells (80). Cox-2 activity is important for the M2 phenotype of TAMs, as inhibition of this enzyme skews TAMs toward an M1 phenotype in tumors of Apc Min/ϩ mice (67).…”
Section: Macrophage Phenotype In Crcmentioning
confidence: 99%
“…Likewise, a recent study suggests that colibactin is not involved on development and maintenance of inflammation. In contrast, the macrophages infiltration into the intestinal epithelium is induced by overgrowth of pks + E. coli strains, and inflammation dependent on COX-2 activation is established (52). Thus, once established the intestinal inflammation, E. coli proliferation is increased and the production of colibactin started after pks island activation.…”
Section: Pks Island and Colibactinmentioning
confidence: 99%